Utility of Serum EB Virus Zta Antibody in the Diagnostic of Nasopharyngeal Carcinoma: Evidences From 2,126 Cases and 15,644 Controls - Zhang, Guangying; Li, Zhanzhan; Zhou, Qin (Frontiers in Oncology, 2019)
We collected previous published data and performed a systematical assessment for the diagnostic value of serum Zta antibody in NPC patients. Using bivariate-mixed effect model, we calculated the sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnosis odds ratio (DOR), and summary receiver operating characteristics curve (AUC) and their 95% confidence intervals (CIs). We also performed subgroup analysis to explore the heterogeneity. We included 23 studies including 24 pieces of data and 17,770 study subjects (2,126 cases and 15,644 controls). The overall combined sensitivity was 0.85 (95%CI: 0.80–0.89) and the combined specificity was 0.90 (95%CI: 0.87–0.93). The summarized AUC was 0.94 with 95%CI of 0.92–0.96. The PLR was 8.9 (95%CI: 6.4–12.2) and the NLR was 0.17(95%CI: 0.12–0.23). The diagnostic odds ratio was 53 (95%CI: 32–87). For publication year, the sensitivity was 0.88 (95%CI: 0.84–0.91) and the specificity was 0.90 (95%CI: 0.84–0.93) for ≤2006. The AUC, PLR, NLR and DOR were 0.94, 8.8, 0.13, and 64. The pooled results were similar for >2006 group. For different sample size, the pooled AUC was 0.94 for ≤Median and was 0.95 for >Median that were very close to the overall estimations. For different population setting, no overlap was found in the sensitivity (0.84 vs. 0.87), specificity (0.90 vs. 0.84), PLR (8.7 vs. 5.5), NLR (0.16 vs. 0.08–0.33), DOR (49 vs. 35), and AUC (0.94 vs. 0.92) between Asian and others. The serum EBV antibody examination has high diagnostic accuracy for early-stage NPC. The diagnostic accuracy seems not to be influenced by sample size, publication year, and ethnic. Considering the few numbers of study with non-Asian population, the present results need to be confirmed in other population setting.